Pre-infarction angina and ischemic pre-conditioning role in coronary reserve protection during early post-infarction period - A. P. Ivanov; T. S. Gornostaeva; I. A. Elgardt (Кардиоваскулярная терапия и профилактика)
Aim. To study coronary reserve features, in regard to angina attacks prior to myocardial infarction (MI) and ischemic pre-conditioning (IPC) phenomenon. Materials and methods. In total, among 78 patients with Q-wave MI, previously diagnosed coronary heart disease (CHD) preceded MI in 61.5% of cases. IPC was diagnosed in 59% of the participants, by repeated stress tests and Holter electrocardiogram monitoring (ECG HM). Results. Both mechanisms of ischemic myocardial protection were associated with better tolerance to physical stress, but had some differences in myocardial ischemia severity. In IPC, myocardial ischemia was characterized by substantial increase in painless ischemic episode rates, with circadian variation in ischemic threshold. Vasospasm might play a role in IPC phenomenon development among MI patients. Therefore, complex study of coronary reserve in such patients, by stress testing with parallel ECG HM, is necessary. Conclusion. IPC and pre-MI angina have protective effects in MI patients. Vasospastic component plays a role in IPC development.